FRI0162 COMPARISON OF MUSCULOSKELETAL INVOLVEMENT OF WRIST AND HAND BY MRI IN TWO SYSTEMIC LUPUS ERYTHEMATOSUS GROUPS: HAND ARTHRITIS AND HAND ARTHRALGIA. (13th June 2020) - Corzo, P.; Garcia-Duitama, I.; Agustí Claramunt, A.; Salman Monte, T. C.; Monfort, J.
Abstract : Background: Articular involvement can reach up to 95% within the multisystemic manifestations of SLE. Originally, a non-erosive pattern of articular inflammation was described, but the emergence of more sensitive imaging techniques, such as Magnetic Resonance Imaging (MRI), show synovitis (S), erosions (E), bone marrow edema (BME) and tenosynovitis (TS) in patients with systemic lupus erythematosus (SLE). Nowadays, a specific validated pattern of articular involvement associated with this disease does not yet exist, although it has begun to be studied (1, 2). Objectives: To asses the extent of structural joint involvement in proximal interphalangeal joints (PIP), hand and wrist: E, BME, S, TS and peritendinitis (PT) by MRI, in patients diagnosed with SLE with hand arthritis or arthralgia. Methods: All patients with SLE who manifested hand pain and/or swelling in the prior 6 months were consecutively included in the study. They were divided into two groups: arthritis or arthralgia, according to the physical examination by an expert rheumatologist. All patients underwent an MRI with contrast injection on their non-dominant hand. The images obtained were evaluated following RAMRIS criteria extended to PIP and Tenosinovitys score for RA by two expert musculoskeletal radiologists, blind to the groups. Results: 32 patients were included: arthritis: n = 13, arthralgia: n = 19, with a mean age of 50.91 ± 13.37 years and a disease evolution time of 10.21 ± 8.26 years. The average SLEDAI score 6.30 ± 3.40 for the arthritis groups and 3.79 ± 2.14 for the arthralgia group. The average SLICC score was 0.23 ± 0.42 in the arthritis group and 0.1 ± 0.31 in the arthralgia group. E was found in 7 patients with arthritis (53.84%) (15.38% in PIP, 0% in hand and 53.84% in wrist) and in 13 patients with arthralgia (68.42%) (0% in PIP, 10.52% in hand and 68.42% in wrist). BME was observed in 4 patients with arthritis (30.76%) (7.69% in PIP, 0% in hand and 30.76% in wrist) and in 5 patients with arthralgia (26.31%) (5.26% in PIP, 10, 52% in hand and 15.78% in wrist). S was observed in 12 patients with arthritis (92.30%) (61.58 in PIP, 76.92% in hand and 84.61% in wrist) and in 8 patients with arthralgia (42.10%) (31.57% in PIP, 36.84% in hand and 36.84% in wrist). TS was observed in 6 patients with arthritis (46.15%) (38.46% in flexor tendons and 23.07% in extensor tendons) and in 8 patients with arthralgia (42.10%) (31.57% in flexor tendons and 21.05 % in extensor tendons). PT was found in 6 patients with arthritis (23.07%) and in no patient with arthralgia (0%) Conclusion: MRI allows us to diagnose musculoskeletal involvement in SLE, morphologically similar to rheumatoid arthritis (erosion, bone marrow edema, synovitis and tenosynovitis), which usually are underestimated on plain radiography. This study also shows the important erosive burden of arthritis in SLE, which has not been well characterised yet. In addition, it demonstrates the underestimation of physical examination to diagnose active inflammatory damage, such as subclinical synovitis, in patients with inflammatory arthralgias. References: [1]Mosca M, Tani C, Carli L, Vagnani S, Possemato N, DelleSedie A, et al. The role of imaging in the evaluation of joint involvement in 102 consecutive patients with systemic lupus erythematosus. Autoimmun Rev. 2015; 14: 10-5 [2]Tani C, D'Aniello D, Possemato N, DelleSedie A, Caramella D, Bombardieri S, Mosca M. MRI pattern of arthritis in systemic lupus erythematosus: a comparative study with rheumatoid arthritis and healthy subjects. Skeletal Radiol. 2015;44:261-6 Disclosure of Interests: None declared